CCIE Voice v3.0 quick references - Lewis, Mark (Cisco Press, 2011)
"As a final exam preparation tool, the CCIE Voice v3.0 quick reference provides a concise review of all objectives on the CCIE Voice written exam v3.0. This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on the technologies and applications that comprise a Cisco Enterprise VoIP solution. This fact-filled quick reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts."--Resource description page.